Relações intergovernamentais em políticas de meio ambiente: o plano nacional de gestão de risco e respostas a desastres (programa 2040) - Indiano, Thais [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to analyze the relationship of the management of the Programme 2040 (Risk management policy and response to disasters) and the decentralization policy of the federative model, in the first year after its insertion in the Brazilian Pluriannual plan. For this, we present through a literature review intergovernmental relations analysis among the federal entities in Brazil and how to divide the implementation of public policies, particularly for the environment. Through the disaster data collection occurred in Brazil preprogram 2040 and program transfers data. We cross the information and seek to identify whether there is a relation between the States that received transfer for risk management and disaster response and the States with the largest number of disasters.

Este trabalho pretende analisar a relação da Gestão do Programa 2040 (Programa de Gestão de Riscos e resposta a desastres) e a descentralização política do modelo federativo, no primeiro ano após sua inserção no Plano Plurianual Brasileiro. Para isso, apresentamos por meio de uma revisão bibliográfica a análise das relações intergovernamentais entre os entes federativos no Brasil e como se dividem na execução de políticas públicas, principalmente de meio ambiente. Através da coleta de dados de desastres acontecidos no Brasil pré-Programa 2040 e dos dados de repasses do Programa, cruzamos as informações e buscamos identificar se há uma relação entre os estados que receberam repasse para realizarem a Gestão de riscos e resposta a desastres e os estados com maior número de desastres.
Keywords: Risk management; Public policies; Federalism; Gestão de riscos; Políticas públicas; Federalismo